PENYULUHAN HUKUM TENTANG BAHAYA NARKOBA BERDASARKAN UNDANG-UNDANG NO. 35 TAHUN 2009 DI KELURAHAN MARGA MULYA RW 08 - Muhammad Rifqy Dwi Saputra; Novita Sari; Susilo Wira Puspita Sari; Alvin Yanuar Handritartha; Gojin Gojali; Oscar Aditya Darmawan; Teuku Radja Iqbal Adamy; Yudha Prasetyo (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Drug abuse is currently a serious concern, involvingvarious groups of society such as students, students, teachers,lecturers, TNI/POLRI, DPR, and even state officials. IndonesianPresident Joko Widodo even called this situation a